Mathematical Creative Thinking and Differences in Students' Cognitive Styles in Learning Achievement: A Systematic Literature Review - Supratman, Supratman; Deti, Deti Sri Rahayu; Sirad, La Ode Sirad (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2024)
The purpose of this article is to explain how students' varied cognitive styles and the outcomes of their mathematical creative thinking interact. The Systematic Literature Review (SLR) method. To find, examine, assess, and interpret all of the research that is currently available on the topic of interest, the SLR technique is employed. All publications pertaining to mathematical creative thinking and cognitive style in student learning achievement are compiled and reviewed in order to gather data. The international journals used were 5 which only focused on Scopus. The results showed that creative thinking can be strengthened in the science curriculum, but empirical evidence supporting the relationship between the two is still limited, but examining the predictive value of creative thinking (divergent and convergent thinking) for scientific reasoning, while considering task specificity and academic achievement, various aspects of divergent thinking (i.e. fluency, flexibility, and originality) benefit from different types of support. Students' fluency scores increased under the full support condition, but decreased in the other two conditions, the FI group had lower and more efficient cognitive load than the FD group. The effect of information load on cognitive load follows a piecewise linear correlation with two prominent nodes, field dependence-independence (FDI) can affect academic performance, selective attention, and working memory. However, the underlying mechanisms of how FDI modulates selective attention and working memory remain unclear, field independence (FDI) may affect academic performance, selective attention, and working memory. However, the underlying mechanism of how FDI modulates selective attention and working memory remains unclear and field-independent students produced better learning achievement but field-dependent students showed higher frustration tolerance, low-ability students experienced more significant improvement than high-ability students. Low ability students also showed higher frustration tolerance.